Perlindungan Hukum Terhadap Perempuan Korban Kekerasan Dalam Rumah Tangga - Nur Fiqri Arif; Sesita Sari; Syarifa Rindiani Putri (CV. ITTC INDONESIA, 2025)
Domestic violence is a serious offense that has a negative impact on victims, especially women, and has become a classic issue in gender relations. This study examines various legal instruments applicable in Indonesia in the context of combating domestic violence, particularly those affecting women as the main victims, such as Law No. 23 of 2004 on the Elimination of Domestic Violence. This study assesses the role of law enforcement officials and related institutions, such as local governments and women's and children's protection agencies, in effectively handling cases of domestic violence against women. In addition, this study highlights the challenges and obstacles faced by women victims of domestic violence in obtaining legal protection. A normative juridical approach is used to assess the effectiveness of existing regulations and recommend strategic steps, including strengthening regulations, raising public awareness of women's rights, and the need for multidisciplinary support to ensure optimal and sustainable protection for women victims of domestic violence in Indonesia.